Assessing job satisfaction and stress among pharmacists in Bulgaria: a cross-sectional study - Evelina Gavazova; Jan Bashev; Kiril Atliev; Daniela Grekova (Pharmacia, 2025)
Pharmacists are increasingly recognized as vital contributors to healthcare systems, with expanding clinical roles and responsibilities. This study aims to evaluate the well-being, job satisfaction, and stress levels among pharmacists in Bulgaria, a country where the pharmaceutical profession is undergoing transformation in alignment with European standards. A cross-sectional survey was conducted using a structured, self-administered 16-item questionnaire distributed online to licensed pharmacists across various practice settings. The survey collected demographic data and explored domains such as job satisfaction, work-related stress, salary perception, and work-life balance. A total of 401 pharmacists participated. Statistical analyses revealed a weak but significant negative correlation between job satisfaction and stress levels and a moderate negative correlation between stress and both work-life balance and salary satisfaction. No significant correlation was found between stress levels and either age or workplace setting. These findings suggest that systemic workplace factors, rather than demographic variables, are the primary drivers of stress among pharmacists. The study concludes that targeted strategies such as improving compensation, promoting job flexibility, and supporting work-life balance are crucial to enhancing pharmacists’ well-being and mitigating burnout. These interventions are essential not only for workforce sustainability but also for maintaining high standards in pharmaceutical care and public health outcomes.